2017
DOI: 10.1177/0022466917720764
|View full text |Cite
|
Sign up to set email alerts
|

A Demonstration Model of Interagency Collaboration for Students With Disabilities: A Multilevel Approach

Abstract: Communicating Interagency Relationships and Collaborative Linkages for Exceptional Students (CIRCLES) is a transition-planning service delivery model designed to guide schools in implementing interagency collaboration. This study examined the impact of CIRCLES on students’ self-determination and participation in individualized education program (IEP) meetings. Forty-four schools located in the Southeast United States were assigned randomly into either the CIRCLES or business-as-usual (BAU) conditions, and 877 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…• One methodologically sound group design study with random assignment (Flowers et al, 2018) Community-based instruction Purchasing skills and social behaviors (e.g., asks for help, says thank you, requests information, greets cashier, says goodbye) 63 participants with ID; 4 participants with autism…”
Section: Ebpsmentioning
confidence: 99%
See 1 more Smart Citation
“…• One methodologically sound group design study with random assignment (Flowers et al, 2018) Community-based instruction Purchasing skills and social behaviors (e.g., asks for help, says thank you, requests information, greets cashier, says goodbye) 63 participants with ID; 4 participants with autism…”
Section: Ebpsmentioning
confidence: 99%
“…CIRCLES is a multilevel intervention that includes interagency collaboration and teaming as a key component to ensure positive postschool outcomes for students with disabilities (Rowe et al, 2019). Results of this review identified one methodologically sound group experimental study with random assignment (Flowers et al, 2018) examining the effects of CIRCLES on students' levels of self-determination and participation in their IEP. Based on this review, there is evidence to support CIRCLES as an RBP.…”
Section: Rbpsmentioning
confidence: 99%
“…Transition must always be a collaborative endeavor—especially when experiencing times that are out of the ordinary such as this current pandemic. Equipping students with the range of experiences, skills, and supports they will need to pursue their personal goals for adulthood requires schools to forge strong relationships with families, adult agencies, employers, and other community members (Flowers et al, 2018). The following addresses the importance of these transition partnerships and highlights strategies for strengthening collaborations beyond the walls of the school.…”
Section: Transition Partnershipsmentioning
confidence: 99%
“…This grant has published one experimental study, one mixed-methods study, and one descriptive study. Results from the experimental study indicated students in the Communicating Interagency Relationships and Collaborative Linkages for Exceptional Students (CIRCLES) condition had higher levels of self-determination and greater Individualized Education Program (IEP) participation than students in the business-as-usual condition (Flowers et al, 2018). Results To evaluate the effects of On the Way Home for students with EBD or LD on (a) parent selfefficacy and empowerment and on the school success of transitioning students, (b) school and placement stability and academic and behavioral functioning, and (c) postintervention outcomes of students and their parents/caregivers…”
Section: Efficacy and Replicationmentioning
confidence: 99%